Manajemen Pembelajaran Sekolah Terpadu (Studi Pada Sekolah Terpadu Al Biruni Makassar) - Sumarlin Mus; Syamsurijal Basri (Publikasi Pendidikan, 2017)
This study reviews the learning management integrated school in Makassar with research sites in an integrated school Al Biruni Makassar. The focus in this research is the learning management in an integrated school which consists of lesson plans, learning implementation, and evaluation. The approach used in this study is a qualitative descriptive approach. The unit of analysis in this research is the principal, teachers, and students. Data collection techniques were interviews, observation, and documentation. The results showed that the learning management consisting of lesson plans, learning implementation, and evaluation of learning has been implemented in accordance with the existing procedures as other schools in general. This integrated concept in this school that is located in its curriculum, which integrates religious values on each of the subjects taught to students.Keywords: Learning Management, Integrated School